Diagnóstico socioeconómico de los propietarios de microemprendimientos comerciales de la calle Francisco Segura, sector suroeste, ciudad de Guayaquil, Ecuador. Guayaquil. ULVR. Facultad de Ciencias Sociales y Derecho Carrera de Economía. 63 p. - Parrales Núñez, Jessica Lisbeth (2024)
The objective of this research is to analyze the socioeconomic situation of commercial microenterprises in the southwest sector of the city of Guayaquil. The methodology of this research is a mixed approach since it presents quantitative and qualitative characteristics; based on descriptive research, through the techniques that were used, which were observation, interview and survey. The interview was applied to an owner who has been in office for the longest time and the surveys were carried out on all the micro-entrepreneurs in the sector, which was evidenced by the surveys that they are mostly men who lead the micro-enterprises who are of age between 19 and 35 years old, the majority of microenterprises do not have the corresponding permits and the largest number of microenterprises receive monthly income ranging between $100 and $350. and the majority do not have their own premises, but rather have to rent; The method that was applied is non-probabilistic sampling, in which 83 microenterprises were identified in said sector..........